Abemaciclib plus trastuzumab with or without fulvestrant versus trastuzumab plus standard-of-care chemotherapy in women with hormone receptor-positive, HER2-positive advanced breast cancer (monarcHER): a randomised, open-label, phase 2 trial. Issue 6 (June 2020) - Tolaney, Sara M; Wardley, Andrew M; Zambelli, Stefania; Hilton, John F; Troso-Sandoval, Tiffany A; Ricci, Francesco; Im, Seock-Ah; Kim, Sung-Bae; Johnston, Stephen RD; Chan, Arlene; Goel, Shom; Catron, Kristen; et al.
Summary: Background: Patients with HER2-positive breast cancer who have received two or more previous therapies for advanced disease have few effective treatment options. The monarcHER trial aimed to compare the efficacy of abemaciclib plus trastuzumab with or without fulvestrant with standard-of-care chemotherapy of physician's choice plus trastuzumab in women with advanced breast cancer. Methods: This phase 2, three-group, open-label trial was done across 75 hospitals, clinics, and medical centres in 14 countries. Eligible patients were women aged 18 years or older, who had hormone receptor-positive, HER2-positive advanced breast cancer with unresectable, locally advanced, recurrent or metastatic disease, Eastern Cooperative Oncology Group performance status of 0 or 1, and who had previously received at least two HER2-targeted therapies for advanced disease. Patients were randomly assigned 1:1:1 to the abemaciclib, trastuzumab, and fulvestrant (group A), abemaciclib and trastuzumab (group B), or standard-of-care chemotherapy and trastuzumab (group C). Oral abemaciclib 150 mg 12 hourly was administered on days 1–21 of a 21-day cycle, intravenous trastuzumab 8 mg/kg on cycle 1 day 1, followed by 6 mg/kg on day 1 of each subsequent 21-day cycle, and intramuscular fulvestrant 500 mg on days 1, 15, and 29 and once every 4 weeks thereafter. Standard-of-care chemotherapy was administered as specified by the product label. Randomisation was by a computer-generated random sequence by means of an interactive web-response system and stratified by number of previous systemic therapies for advanced breast cancer and measurable versus non-measurable disease. The primary endpoint was investigator-assessed progression-free survival in the intention-to-treat population, first testing group A versus group C and, if this result was significant, then group B versus group C. Safety was assessed in all patients who had received at least one dose of study treatment. This trial is registered at ClinicalTrials.gov (NCT02675231 ) and is ongoing for long-term survival follow-up. Findings: Between May 31, 2016, and Feb 28, 2018, 325 patients were screened, of whom 237 eligible patients were enrolled and randomly assigned to groups A (n=79), B (n=79), and C (n=79). Median follow-up was 19·0 months (IQR 14·7–25·1). The study met its primary endpoint, showing a significant difference at the prespecified two-sided α of 0·2 in median progression-free survival between group A (8·3 months, 95% CI 5·9–12·6) and group C (5·7 months, 5·4–7·0; HR 0·67 [95% CI 0·45–1·00]; p=0·051). No difference was observed between median progression-free survival in group B (5·7 months, 95% CI 4·2–7·2) and group C (HR 0·94 [0·64–1·38]; p=0·77). The most common grade 3–4 treatment-emergent adverse event in groups A, B, and C was neutropenia (21 [27%] of 78 patients, 17 [22%] of 77, and 19 [26%] of 72). The most common serious adverse events were: in group A, pyrexia (three [4%]), diarrhoea (two [3%]), urinary tract infection (two [3%]), and acute kidney injury (two [3%]); in group B, diarrhoea (two [3%]) and pneumonitis (two [3%]); and in group C, neutropenia (four [6%]) and pleural effusion (two [3%]). Two deaths were attributed to treatment: one due to pulmonary fibrosis in group B and one due to febrile neutropenia in group C. Interpretation: The combination of abemaciclib, fulvestrant, and trastuzumab significantly improved progression-free survival versus standard-of-care chemotherapy plus trastuzumab while showing a tolerable safety profile. Our results suggest that a chemotherapy-free regimen might potentially be an alternative treatment option for patients with hormone receptor-positive, HER2-positive advanced breast cancer. Funding: Eli Lilly and Company.